The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1161/circulationaha.112.114173
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Mediate the Cytoprotective Action of Mesenchymal Stromal Cells on Hypoxia-Induced Pulmonary Hypertension

Abstract: Background Hypoxia induces an inflammatory response in the lung manifested by alternative activation of macrophages with elevation of pro-inflammatory mediators that are critical for the later development of hypoxic pulmonary hypertension (HPH). Mesenchymal stromal cell (MSC) transplantation inhibits lung inflammation, vascular remodeling and right heart failure, and reverses HPH in experimental models of disease. In this study, we aimed to investigate the paracrine mechanisms by which MSCs are protective in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
577
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 692 publications
(608 citation statements)
references
References 51 publications
10
577
2
5
Order By: Relevance
“…Bruno et al 68,71 Microvesicles derived from human MSCs had protective eff ects in both in-vitro and in-vivo acute kidney injury models Lee et al 72 Intravenous administration of MSC-derived exosomes decreased the infl ux of infl ammatory mediators and inhibited vascular remodelling and pulmonary hypertension in a murine model of hypoxia-induced pulmonary hypertension…”
Section: Summary Extracellular Vesiclesmentioning
confidence: 99%
“…Bruno et al 68,71 Microvesicles derived from human MSCs had protective eff ects in both in-vitro and in-vivo acute kidney injury models Lee et al 72 Intravenous administration of MSC-derived exosomes decreased the infl ux of infl ammatory mediators and inhibited vascular remodelling and pulmonary hypertension in a murine model of hypoxia-induced pulmonary hypertension…”
Section: Summary Extracellular Vesiclesmentioning
confidence: 99%
“…31,54,67 STROMAL CELL-DERIVED EXOSOMES AND MICROVESICLES Exosomes and microvesicles are small but complex entities that contain both immunomodulatory proteins and microRNA, and have homing abilities. 68 69 MSC-derived microvesicles have been shown to protect from acute kidney injury, 70 myocardial ischemia 71 and pulmonary hypertension 72 in animal models ( Table 3). The regenerative capacities of microvesicles appear to be at least partly dependent on the mRNA cargo, as treatment with RNAase to inactivate the mRNA content abrogated the protective effects.…”
Section: Cd39 and Cd73mentioning
confidence: 99%
“…14 Interestingly, miR-204 has already been shown to be decreased in plexiform vasculopathy of severe PAH in humans, 49 predicted to be a disease-modifying miRNA in PAH, 50 and established as a critical actor in a hypoxia-induced pulmonary hypertension mouse model. 51 Abated miR-204 levels were also associated with decreased apoptosis, enhanced cell proliferation, 52 and membrane depolarization, 53,54 the most common alterations observed in PAH-PASMC. In addition, it has been shown that this pro-proliferative phenotype is associated with activation of the Src-STAT3 and NFAT pathway (Fig.…”
Section: Molecular Contribution Of Pasmcs To Pah Phenotypementioning
confidence: 99%